DETERMINATION OF THE ISSUE CONCERNING THE LIFT RESISTANCE FACTOR OF LIGHTWEIGHT CAR - Shvets, A. O.; Zhelieznov, K. I.; Akulov, A. S.; Zabolotnyi, O. M.; Chabaniuk, Ye. V. (Science and Transport Progress, 2015)
Purpose. The analytical study of the connection between the longitudinal force, acting on the light-weight car, lateral and vertical forces of interaction in the contact zone «wheel – rail» with the lift resistance factor value is to provide a simple relationships between them. Methodology. Research was conducted by the method of mathematical modeling of loading the freight car when driving at different speeds on straight and curved sections of a track. Findings. Even in the absence of «lift» accordingly the classical train stability theory, as the hinge-rod system, the presence of the longitudinal compressive forces may become a factor provoking cars derailment. The main reason of wheel climbing on rails is the combination of processes of dynamic interaction between the hunting vehicle and the track with simultaneous action of longitudinal compressive forces, and not the destabilization of train as a hingedrod system. To assess the impact of the longitudinal forces value on the lift resistance factor there are presented the calculation results for the empty gondola car motion, model No. 12-532, on 250 m radius curve with 150 mm rise and cross starting of car underframe relating to the track axis in 50 mm guiding section. The calculations were made in such a curve excluding the inertial forces from outstanding acceleration and taking into account the unbalanced acceleration with the permissible speed of 65 km/h. Originality. This study provides the technique of determining the lift resistance factor by longitudinal forces, which is somewhat different from the standard one, as well as evaluates impact of rolling stock speed on this factor. Practical value. The authors clarify the current method of determining the lift resistance factor by longitudinal forces and assess the impact of rolling stock speed on the value of this factor. From these studies one can conclude that because of cars hunting their lift is possible even when the train as hinge-rod system does not lose stability. The developed proposals allow reducing the number of car derailment by taking into account important parameters and characteristics during the process of calculation and design that increase their stability in the rail track especially in case of increased speed of freight trains.